Rare case report: primary small-cell neuroendocrine carcinoma of the gallbladder - Wang, Haichen; Li, Qinglin; Han, Shaoqi; Tian, Hu (Frontiers in Oncology, 2025)
Gallbladder cancer (GBC) accounts for 1.7% of all cancer-related deaths. Neuroendocrine carcinoma of the gallbladder (GB-NEC) is a rare subtype of GBC that is more malignant than GBC. Small-cell neuroendocrine carcinoma of the gallbladder (GB-SCNEC) is a rare malignant tumor with a low incidence. To date, no universally accepted or satisfactory treatment exists. This case report details the clinical presentation, diagnostic process, and treatment strategy of a patient with GB-SCNEC. The analysis of this rare case is intended to provide clinicians with diagnostic and therapeutic insights for future research.